Scorched Earth: Employers’ Breached Trust in Refugees’ Labor Market Integration - Wehrle, Katja; Kira, Mari; Klehe, Ute-Christine; Hertel, Guido; Justus Liebig University Giessen (My University, 2024)
Employment is critical for refugees’ positive integration into a receiving country. Enabling employment requires cross-sector collaborations, that is, employers collaborating with different stakeholders such as refugees, local employees, other employers, unofficial/official supporters, and authorities. A vital element of cross-sector collaborations is trust, yet the complexity of cross-sector collaborations may challenge the formation and maintenance of trust. Following a theory elaboration approach, this qualitative study with 37 employers and 27 support workers in Germany explores how employers’ experiences in cross-sector collaborations on refugees’ labor market integration affect their trust in other stakeholders in this cross-sector space. Specifically, we explored employers’ perceptions of trust breaches, and how these perceptions affect their further engagement in cross-sector collaborations on refugee integration. Based on our findings, we propose a process model that describes how unmet collaboration expectations and negative assessments of collaborators’ attitudes and behaviors lead to perceived trust breaches which, in turn, lead to employers’ hesitancy to hire refugees and/or to engage in cross-sector collaborations. In doing so, we extend existing theory on trust within organizations to the cross-sector context of refugee integration, uncovering context-specific meanings to trustworthiness dimensions and illustrating how breaches of different trustworthiness dimensions can interact. Moreover, we show how social policies, resources, and trustors’ perceived vulnerability in collaborations shape their risk perceptions. This study highlights the central role of trust for refugee integration and illustrates how missing goals and process clarity endanger sustainable collaborations.
Keywords: ddc:150